Strategi Komunikasi Pemasaran Dalam Meningkatkan Brand Awareness Pada Transportasi Online ‘Jasaku Aek Kanopan’ - Rizka Azzura, Putri; Hidayat, Rahmat (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2026)
Competition in the online transportation industry requires every service provider to be able to build strong brand awareness to remain remembered and chosen by consumers. This study aims to analyze the marketing communication strategy implemented by JASAKU in increasing brand awareness as a local online transportation service in Aek Kanopan City. The study used a qualitative descriptive method with data collection techniques through observation, interviews and documentation. The research informants consisted of JASAKU owners and five consumers. The results of the study indicate that JASAKU's marketing communication strategy reflects the implementation of integrated marketing communication (IMC) through a combination of conventional communication, digital communication and mutually supportive public relations activities. This strategy is carried out through interpersonal communication, the use of social media Instagram and Facebook, and involvement in community social activities. The research findings show that the majority of consumers place JASAKU at the top of mind level, while others are at the brand recall level. This condition indicates that the implemented marketing communication strategy is able to strengthen JASAKU's brand awareness among the people of Aek Kanopan City.